2021
DOI: 10.1029/2021gl093238
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Transboundary‐Local Aerosols Interaction Over Complex Terrain Using a Doppler LiDAR Network

Abstract: Transboundary‐local aerosols interaction requires to be comprehensively understood in urban air quality research. A year‐long intensive observation of the atmospheric boundary layer (ABL) at multiple sites in Hong Kong was conducted using a four‐Doppler Light Detection and Ranging (LiDAR) network with different scanning modes. Results show that heterogeneity of the ABL in terms of mixing layer height and wind shear was induced by orographic topography. Interaction between local and advected aerosol layers duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…The Doppler LiDAR installed at King's Park (Yim, 2020) is shown in Figure 1(b). It is a Halo Photonics 1.5‐μm pulsed Doppler instrument, which has been used in studies exploring the characteristics of the planetary boundary layer in the tropical and mid‐latitude environments (Yang et al ., 2019; Huang et al ., 2020, 2021a,b, 2022; Yim, 2020; Yim and Tao, 2022). The instrument was fixed on a concrete foundation in a flat grass field, at an altitude of 65m amsl.…”
Section: King's Park Meteorological Station and The Lidar Instrumentmentioning
confidence: 99%
“…The Doppler LiDAR installed at King's Park (Yim, 2020) is shown in Figure 1(b). It is a Halo Photonics 1.5‐μm pulsed Doppler instrument, which has been used in studies exploring the characteristics of the planetary boundary layer in the tropical and mid‐latitude environments (Yang et al ., 2019; Huang et al ., 2020, 2021a,b, 2022; Yim, 2020; Yim and Tao, 2022). The instrument was fixed on a concrete foundation in a flat grass field, at an altitude of 65m amsl.…”
Section: King's Park Meteorological Station and The Lidar Instrumentmentioning
confidence: 99%
“…In addition to localized air pollution, transboundary air pollution has emerged as a crucial factor exacerbating air pollution on global (Holloway et al., 2003), regional (Gu & Yim, 2016; Hou et al., 2019), and local scales (Tong et al., 2018; Huang, Li, et al., 2021). Particularly, transboundary haze stemming from biomass burning has been a prominent issue throughout Southeast Asia (Hansen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies focused on improving model performance, few of them attempted to evaluate the contribution of different factors on air pollutants, which is particularly important for cities with air pollution influenced not only by their local sources but also by transboundary pollution from neighboring regions. , To understand air pollutant concentration effectively, contributions of different driving factors (i.e., emission sources and meteorological factors) , to air quality should be analyzed comprehensively. For example, numerous studies reported that the East Asian region including South Korea has been affected by transboundary air pollution , that can be driven by favorable meteorological conditions for long-range air pollutant transport.…”
Section: Introductionmentioning
confidence: 99%